Variations in activity of Ru/TiO(2 )and Ru/Al2O3 catalysts for CO2 hydrogenation: an investigation by in-situ infrared spectroscopy studies - Dongapure, Pavan; Bagchi, Sayan; Mayadevi, S.; Devi, R. Nandini (Molecular Catalysis, 2020)
CO2 hydrogenation to methane, an important reaction strategically and also for value adding to CO2, is investigated on two different catalysts, Ru supported on alumina as well as titania to understand better low temperature activity of Ru/TiO2 catalyst. In-situ infrared studies are carried out in three different steps, viz., (i) CO2 adsorption on fully reduced catalyst (ii) reaction of these adsorbed species with gaseous H-2 and (iii) under co-feed of CO2 and H-2, at different temperatures. On Ru/Al2O3 catalyst, CO2 reacts with hydroxyls on the support surface to form carbonate and adsorbs reductively on metal as CO. Further reduction to formate and methyl species occurs on reaction with H. Small concentration of the reactive intermediate formyl forms only at high temperatures. Whereas, bare TiO2 itself seems capable of reductive adsorption of CO2 as formate indicating enhanced reducibility of titania based catalyst. Formyl groups are observed at low temperatures in Ru/TiO2 in step (ii), which further forms methyl and gaseous methane at much lower temperatures when compared to alumina catalyst. Highly reactive CO species loosely bound to metal-support interface observed at high temperatures, which is not present on Ru/Al2O3 catalyst also makes this catalyst superior. In comparison, linearly bound CO seen in alumina catalyst is not as reactive.
Keywords: CO2 hydrogenation; In-situ infra red spectroscopy; Ru/Al2O3; Ru/TiO2

Viscosity effects on the dynamics of diols and diol-based deep eutectic solvents - Chatterjee, Srijan; Deshmukh, Samadhan H.; Chowdhury, Tubai; Bagchi, Sayan (Photochemistry and Photobiology, 2024)
Diols, characterized by the presence of two hydroxyl groups, form extended hydrogen-bonded networks. Increasing hydrocarbon chain length is known to elevate the viscosity of diols. Given the established influence of viscosity on solvent dynamics, it becomes imperative to comprehend the impact of viscosity on the fluctuation dynamics within diols and establish connections with hydrogen bond formation and breaking dynamics. In this study, we employ two-dimensional infrared spectroscopy to investigate the viscosity dependence of the structural evolution dynamics in three diols with varying chain lengths. Complementing our experimental approach, molecular dynamics simulations are conducted to extract hydrogen bond lifetimes. Our findings reveal a linear correlation between bulk viscosity, solvent fluctuation timescales, and hydrogen bond lifetimes. Notably, the selected diols exhibit the capability to form deep eutectic solvents upon mixing with choline chloride at specific molar ratios. In contrast to molecular solvents like diols, deep eutectic solvents are characterized by the formation of heterogeneous nanodomains, comprising various intercomponent hydrogen-bonded networks. Interestingly, our observations indicate that while the fluctuation dynamics decelerate with increasing bulk viscosity in diol-based deep eutectic solvents, the relationship between viscosity and dynamics is not linear, in contrast to the observed linearity in diols. This nuanced understanding contributes to the broader comprehension of the interplay between viscosity and dynamics in both molecular and deep eutectic solvents. We investigate the impact of viscosity on structural evolution dynamics in diols with varying chain lengths. Employing two-dimensional infrared spectroscopy and molecular dynamics simulations, we explore the relationship between bulk viscosity, solvent fluctuation timescales, and hydrogen bond lifetimes. We report a linear correlation in diols between viscosity, fluctuation timescales, and hydrogen bond lifetimes. Diols also form deep eutectic solvents, characterized by heterogeneous nanodomains. While fluctuation dynamics slow down with increasing bulk viscosity in diol-based deep eutectic solvents, the relationship between viscosity and dynamics is nonlinear, contrasting with diols' linearity. This understanding enhances comprehension of viscosity-dynamics interplay in molecular and deep eutectic solvents.image
Keywords: Dynamics; Hydrogen bond; solvent; spectroscopy; viscosity